Tagasaste tree could rival Leucaena - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Tagasaste (Chamaecytisus almensis) a small scrubby highland nitrogen-fixine tree, which shares some of the attributes of Leucaena and could be used in tropical highlands and Mediterranean climates for fodder and fuelwood. The tree is indigenous to...